Wireless edge intelligence empowers smart society - Zhi WANG; Xing ZHANG; Wenbo WANG (Dianxin kexue)
To satisfy the technical requirements of eMBB,mMTC and uRLLC in 5G application scenarios,wireless edge intelligence sinks core capabilities of computing,caching and network to the edge of radio access network,as well as introduces technologies such as deep learning/artificial intelligence into the edge cloud,thereby enabling digital life,digital society and digital industry.Firstly,the concept,challenges and opportunities of wireless edge intelligence were clarified.Moreover,the platform deployment of wireless edge intelligence was analyzed.Finally,the possible future deployment directions of wireless edge intelligence were discussed.